Bright red aggregation-induced emission nanoparticles for multifunctional applications in cancer therapy. Issue 9 (29th January 2020) - Zhang, Liping; Che, Weilong; Yang, Zhiyu; Liu, Xingman; Liu, Shi; Xie, Zhigang; Zhu, Dongxia; Su, Zhongmin; Tang, Ben Zhong; Bryce, Martin R.
Abstract : Developing multifunctional photosensitizers (PSs) is needed to effectively simplify cancer treatment, but it remains a big challenge. Abstract : Developing multifunctional photosensitizers (PSs) is needed to effectively simplify cancer treatment, but it remains a big challenge. Here, two red-emitting AIE-active, donor–acceptor (D–A) PSs with small Δ E ST and their AIE nanoparticles, are rationally designed and synthesized. The PS1 NPs exhibit bright red-emission with high quantum yield, appropriate 1 O2 generation ability and good biocompatibility. More importantly, PS1 NPs can strongly light up the cytoplasm by gently shaking the cells for only 5 s at room temperature, indicating ultrafast staining and mild incubation conditions. In vitro and in vivo cell tracing demonstrate that PS1 NPs can track cells over 14 days, and effectively inhibit tumor growth upon irradiation. To the best of our knowledge, this work is the first example of a PS that integrates image-guided PDT, ultrafast staining and long-term tracing functions, demonstrating the "all-in-one" concept which offers great advantages for potential clinical applications.